Co-occurrence of intraoral hemangioma and port wine stain: A rare case - Prasanna Kumar Rao; Vishal Bejai; Sanath Rao; Shishir Ram Shetty (Wolters Kluwer Medknow Publications, 2012)
Hemangiomas are neoplastic proliferations of endothelial cells, characterized by a period of growth after birth, and eventual spontaneous involution. The course can be uneventful with spontaneous resolution; or it may be marked by complications such as infection, bleeding, ulceration, visual defects and feeding difficulties. Apart from these, rare life-threatening complications such as congestive heart failure and consumption coagulopathy may also be seen. Although hemangiomas commonly occur in the head and neck region, intraoral occurrence is relatively rare. A port wine stain is defined as a macular telangiectatic patch which is present at birth and remains throughout life. They may be localized or extensive, affecting a whole limb. This article reports a rare case of co-occurrence of port wine stain with intraoral hemangioma.